PETROELECTRICAL INVESTIGATIONS OF BOREHOLE CORE OF COMPLEXLY-BUILD RESERVOIR ROCKS - VYZHVA, S.; REVA, M.; HOZHYK, A.; ONYSHCHUK, V.; ONYSHCHUK, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The features of method and results of petroelectrical investigation of complex-structured terrigenous reservoir are considered. As well results of determination of specific electric resistance and his connection with capacity and filtration properties of 33 sample’s collection in the laboratory conditions and modeling of rock unit conditions.